India : Country Framework Report for Private Participation in Infrastructure - World Bank (Washington, DC, 2013)
This Country Framework Report for India is the first in a series of country reviews aimed at improving the environment for private sector involvement in infrastructure. Prepared at the request of the government concerned, Country Framework Reports have three main objectives: 1) To describe and assess the current status and performance of key infrastructure sectors. 2) To describe and assess the policy, regulatory, and institutional environment for involving the private sector in those sectors. 3) Through the above, to assist policymakers in framing future reform and development strategies and to assist potential private sector investors in assessing investment opportunities. This country framework report undertakes a sectoral review in Part I examining telecommunications, power, urban water and sewer systems, roads, ports, and airports. For each sector the report analyzes market structure and performance, private sector participation, and regulatory environment, and makes policy recommendations. Part 2 discusses the development of the infrastructure regulatory institutions, the role of the domestic debt market in infrastructure finance, and the public-private interface, specifically contracting and implementing project, risk sharing, and environmental and social impact legislation. Part 3 comprises a summation of the policy recommendations offered for each sector and the three topics elucidated in Part 2.